Severe thrombocytopenia induced by tirofiban after percutaneous coronary intervention: a case report - Ze-Mu Wang; Bin Wang; Ya-Fei Li; Bei Chen; Qin Shen; Dian-Fu Li; Lian-Sheng Wang (Journal of Medical Case Reports, 2023)
Abstract Background Tirofiban is a nonpeptide glycoprotein IIb/IIIa receptor antagonist used widely in patients subjected to percutaneous coronary intervention. While the usage of tirofiban sets an important clinical benefit, severe thrombocytopenia can occur with use of this agent. Case presentation A 76-year-old Chinese man was admitted with 1-month history of sudden onset of chest tightness. He was diagnosed as having subacute inferior myocardial infarction, and percutaneous coronary intervention was performed. After the procedure, patient received tirofiban at 0.15 µg/kg/minute for 4 h. A blood sample was obtained for a complete blood count; severe thrombocytopenia was reported according to routine orders at our hospital. All antiplatelet drugs including tirofiban, aspirin, and clopidogrel were immediately discontinued. The patient received platelet transfusions and was treated with immunoglobulin G. Two days later, the patient’s platelet count had increased to 75 × 109/L. There was a significant improvement after day 5, and the platelet count was 112 × 109/L. Seven days after the acute thrombocytopenia, he was discharged with normal platelet count. Conclusions Clinicians should be particularly aware of tirofiban-induced thrombocytopenia in routine practice.